2021
DOI: 10.1002/jmv.27141
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory parameters related to severe disease and death in SARS‐CoV‐2 pneumonia: Retrospective analysis

Abstract: The clinical evolution of coronavirus disease 2019 (COVID‐19) is highly variable and hospitalized patients can rapidly develop conditions requiring oxygen support, intensive care unit (ICU) or high dependency unit (HDU) care. Early identification of high‐risk patients is mandatory. We retrospectively collected the medical history, symptoms, radiological, and laboratory findings of COVID‐19 patients hospitalized between February and April 2020. Laboratory data were collected at the first, last, and middle times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Strong evidence has been accumulated since the beginning of the COVID-19 pandemic that neutrophils play an important role in the pathogenesis of severe disease course and that neutrophilia represents a feasible and inexpensive biomarker of COVID-19 severity ( Wu et al, 2020 ). In COVID-19 patients, neutrophilia associated with lymphopenia was observed in patients with increased disease severity and with poor prognosis ( Picchi et al, 2021 , Yang et al, 2020 , Zhu et al, 2021 ). A number of studies showed a correlation between markers derived from standard blood count tests, such as neutrophil-to-lymphocyte ratio (NLR), derived NLR ratio (dNLR, neutrophil count divided by the result of WBC count minus neutrophil count), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) and systematic inflammatory response in a number of age-related diseases, including cancer ( Xu et al, 2021 , Ying et al, 2014 ), type 2 diabetes mellitus (T2DM) ( Tong et al, 2004 ), cardiovascular diseases (CVD) ( Bhat et al, 2013 , Ji et al, 2021 ), and stroke ( Cai et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence has been accumulated since the beginning of the COVID-19 pandemic that neutrophils play an important role in the pathogenesis of severe disease course and that neutrophilia represents a feasible and inexpensive biomarker of COVID-19 severity ( Wu et al, 2020 ). In COVID-19 patients, neutrophilia associated with lymphopenia was observed in patients with increased disease severity and with poor prognosis ( Picchi et al, 2021 , Yang et al, 2020 , Zhu et al, 2021 ). A number of studies showed a correlation between markers derived from standard blood count tests, such as neutrophil-to-lymphocyte ratio (NLR), derived NLR ratio (dNLR, neutrophil count divided by the result of WBC count minus neutrophil count), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) and systematic inflammatory response in a number of age-related diseases, including cancer ( Xu et al, 2021 , Ying et al, 2014 ), type 2 diabetes mellitus (T2DM) ( Tong et al, 2004 ), cardiovascular diseases (CVD) ( Bhat et al, 2013 , Ji et al, 2021 ), and stroke ( Cai et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Valores de corte para marcadores biológicos y sus OR de asociación con un desenlace fatal. Al igual que en otros estudios clínicos, observamos que la edad, probablemente debido a una mayor presencia de comorbilidades, y el mayor índice de masa corporal se asociaron con un peor pronóstico y una mayor mortalidad en estos pacientes (30)(31)(32) . La obesidad afectaría a los pacientes con COVID-19 a través de varios mecanismos distintos.…”
Section: Análisis Estadísticounclassified